Nivel de cumplimiento de la distribución de gastos del FONCOMUN y su efecto en el pago de proveedores de la Municipalidad Distrital de Calzada - Provincia de Moyobamba - año 2013 - Garay Garcia, Heidy (2015)
Determine the level of compliance with the distribution of expenses of the FONCOMUN and its effect on the payment to suppliers of the district municipality of road, year 2013, is the product of the analysis on the problems related to the fulfillment of the distribution of expenses of the FONCOMUN and its effect on the payment to suppliers of the entity reference. A design was used mixed (qualitative and quantitative), which took place a descriptive explanatory study that aims to observe, describe , analyze, interpret the execution of the FONCOMUN costs and determine the level of compliance of the expenditure distribution. While the FONCOMUN cost-sharing is approved in the institutional budget of opening (PIA), this is not enforced generating a high non-compliance with the distribution of expenses affecting the fulfilment of payments to suppliers. It has come to the conclusion that the main factors that does not comply with the distribution of expenses of the FONCOMUN is that their needs are greater than resources received and Municipal management does not meet cost-sharing percentages .